# What transformation can you apply to #y=sqrtx# to obtain the graph #y=3sqrt(-x)-4#?

- Stretch by factor of
#3# . - Reflect over y-axis.
- Shift
#4# units downward.

- Multiplying by
#3# stretches the graph by a factor of#3# . - Multiplying
#x# by#-1# reflects the graph over the y-axis. - Subtracting
#4# from the entire equation shifts the graph downwards#4# units.

By signing up, you agree to our Terms of Service and Privacy Policy

To transform the graph of ( y = \sqrt{x} ) to ( y = 3\sqrt{-x} - 4 ), you can follow these steps:

- Reflect the graph of ( y = \sqrt{x} ) about the y-axis to account for the negative sign before the x under the square root.
- Stretch the reflected graph vertically by a factor of 3, which will change the steepness of the graph.
- Shift the stretched graph downward by 4 units to achieve the desired vertical shift.

The resulting graph will be ( y = 3\sqrt{-x} - 4 ).

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you determine whether the function #f(x)=3x+5# has an inverse and if it does, how do you find the inverse function?
- What are the asymptotes for #y=1/(x+3)#?
- How do you find the inverse of #y=3x^2-2# and is it a function?
- How do you find the asymptotes for #y=3/(2x-1)#?
- How do you find vertical, horizontal and oblique asymptotes for #f(x)={ x^2 - 81 }/ {x^2 - 4x}#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7